Structure аnd Physical-Mechanical Properties of nc-TiN Coatings Obtained by Vacuum-Arc Deposition and Deposition of HF Discharge - A.P. Sypylenko; R.Y. Tkachenko; G.V. Kirik; I.T. Karasha; A.M. Mahmud; A.D. Pogrebnyak (Журнал нано- та електронної фізики)
Using scanning electron microscopy (SEM), rengen-structural analysis (RSA), adhesion strength, friction coefficient and wear rate of the material and studied the properties of the coatings nc – TiN. Depending on the bias potential applied to the substrate and the chamber pressure, the inclusion of HF discharge, it is shown that the combination of different parameters recorded during scratching, allows us to distinguish the threshold of critical loads that are linked to different types of cohesive and adhesive fracture coatings in tribological tests. Sizes were determined nanograins nc – TiN stoichiometry of coatings, as well as the phase of elemental composition and morphology of the surface flooring.